1987
DOI: 10.1192/bjp.150.2.180
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbamazepine and Lithium on Remission from Affective Illness

Abstract: Times in remission from affective illness were prolonged during treatment with lithium carbonate and carbamazepine, but lithium was the more effective. Similar global scores for the two drugs suggested that other factors may determine their acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 9 publications
2
43
0
2
Order By: Relevance
“…It would have been difficult to carry out a blind study over 2.5 years with two substances that present a clearly different side effect profile. In the study on lithium and carbamazepine of Watkins et al [43] blindness could not be kept, and there has been serious doubt in the validity of the double-blind design in long-term trials [44]. In our study, it cannot be excluded that because of the more recent introduction of carbamazepine as a mood stabilizer, the physicians were less confident in the efficacy of carbamazepine as compared to lithium.…”
Section: Discussionmentioning
confidence: 43%
“…It would have been difficult to carry out a blind study over 2.5 years with two substances that present a clearly different side effect profile. In the study on lithium and carbamazepine of Watkins et al [43] blindness could not be kept, and there has been serious doubt in the validity of the double-blind design in long-term trials [44]. In our study, it cannot be excluded that because of the more recent introduction of carbamazepine as a mood stabilizer, the physicians were less confident in the efficacy of carbamazepine as compared to lithium.…”
Section: Discussionmentioning
confidence: 43%
“…Several controlled studies corroborated carbamazepine's effectiveness in the acute treatment of mania and perhaps prophylaxis of the disorder (Okuma et al 1979(Okuma et al , 1990Coxhead et al 1992;Lusznat et al 1988;Small et al 1991;Watkins et al 1987). Most studies found it to be comparable to lithium in effectiveness, except for three studies (Okuma et al 1981;Lerer et al 1987;Watkins et al 1987).…”
Section: Carbamazepinementioning
confidence: 86%
“…Most studies found it to be comparable to lithium in effectiveness, except for three studies (Okuma et al 1981;Lerer et al 1987;Watkins et al 1987). However, for prophylactic treatment, according to a recent meta-analysis of this literature (Dardennes et al 1995), the effectiveness of carbamazepine remains to be established.…”
Section: Carbamazepinementioning
confidence: 99%
“…When comparing these results to other studies we were confronted with the fact that our patients did somewhat better than those reported by other investigators [10,12,16,17], This might be due to the fact that only about 25% of our sample had been Li nonresponders, a group of patients that clearly prevailed in other studies. It could be argued that Li nonresponders are also less likely to respond to CBZ, and thus show less treatment response than our group consisting mainly of prophylaxis-naive patients.…”
Section: Discussionmentioning
confidence: 41%